Alterations on cellular redox states upon infection and implications for host cell homeostasis - Mesquita, Inês Morais (2018)
The cofactors nicotinamide adenine dinucleotide (NAD+) and its phosphate form, NADP+, are crucial molecules present in all living cells. The delicate balance between the oxidized and reduced forms of these molecules is tightly regulated by intracellular metabolism assuring the maintenance of homeostatic conditions, which are essential for cell survival and proliferation. A recent cluster of data has highlighted the importance of the intracellular NAD+/NADH and NADP+/NADPH ratios during host-pathogen interactions, as fluctuations in the levels of these cofactors and in precursors' bioavailability may condition host response and, therefore, pathogen persistence or elimination. Furthermore, an increasing interest has been given towards how pathogens are capable of hijacking host cell proteins in their own advantage and, consequently, alter cellular redox states and immune function. Here, we review the basic principles behind biosynthesis and subcellular compartmentalization of NAD+ and NADP+, as well as the importance of these cofactors during infection, with a special emphasis on pathogen-driven modulation of host NAD+/NADP+ levels and contribution to the associated immune response.